Power distribution network design with split and merged power rails. Issue 4 (1st July 2014) - Chew, Li Wern
Abstract : In a power distribution network design, it is always desirable to have a clean, undistorted power supply from the voltage source to each of the functional blocks in a microprocessor in order for the chip to function properly. Although a large individual power rails supply is generally preferred, it is usually not feasible in a real‐world design due to form factor limitation and cost constraint. Power rails merging not only allows the option for decoupling capacitors sharing, but also reduces the number of voltage sources needed in the designed system. However, by merging power rails, coupling noise is generated between the functional blocks that share the same voltage source. In this study, a study on power rails merger option is carried out based on two aspects: the load current characteristics and the power noise tolerances of the functional blocks being merged.